Pendidikan Kewarganegaraan: usaha konkret memperkuat multikulturalisme di Indonesia - Wibowo, Arif Prasetyo; Wahono, Margi (Universitas Negeri Yogyakarta, 2017)
Civic Education has a strategic role in strengthening multiculturalism in Indonesia. However, the contents of civic learning at the elementary level up to university level are showing lack of phenomenon that explores the multicultural values based on local wisdom (local genius). This research is a literature study by finding reference theories relevant to the cases or problems found. The reference theory obtained by method of literature study was presented as the foundation. It was found that: (1) The primordially knowledge, attitude and behavior of Indonesian society are kinds of things that impede Civics Education as a medium for strengthening multiculturalism in Indonesia; (2) Civic Education has great potential to become the foundation for multicultural strengthening in Indonesia with attention to innovation and development of the content, as well as the learning model. (3) Civic Education has a philosophical meaning as the foundation of ligature strength in the establishment of pluralism multicultural mentalities in order to realize national goals and nation's modernization without abandoning the local wisdom.